The Prognosis of Severe Acute Pancreatitis Varies According to the Segment Presenting With Low Enhanced Pancreatic Parenchyma on Early Contrast-Enhanced Computed Tomography: A Multicenter Cohort Study. Issue 7 (August 2017) - Kitamura, Katsuya; Horibe, Masayasu; Sanui, Masamitsu; Sasaki, Mitsuhito; Yamamiya, Akira; Ishii, Yu; Yoshida, Hitoshi; Sawano, Hirotaka; Goto, Takashi; Ikeura, Tsukasa; Hamada, Tsuyoshi; Oda, Takuya; et al.
Abstract : Objective: The aim of this study was to investigate the outcomes of severe acute pancreatitis (SAP) according to the segment presenting with low enhanced pancreatic parenchyma (LEPP) on early contrast-enhanced computed tomography. Methods: This was a post hoc analysis of a multicenter, retrospective study conducted at 44 institutions in Japan. Patients diagnosed as having SAP according to the Japanese Severity Score between January 2009 and December 2013 were included. We compared the effect of LEPP in each segment on mortality. Results: A total of 1097 patients were assessed. The numbers of patients with LEPP in the pancreatic head (Ph), body (Pb), or tail (Pt) were 272, 273, and 204 (with some overlaps), respectively. In multivariate analysis, LEPP in Ph and Pt was significantly related to mortality (odds ratio [OR], 1.94; 95% confidence interval [CI], 1.11–3.40 [ P < 0.05], for LEPP in Ph; OR, 2.44; 95% CI, 1.27–4.67 [ P < 0.05], for LEPP in Pt), but LEPP in Pb was unrelated to mortality (OR, 0.70; 95% CI, 0.35–1.37; P = 0.30). Conclusions: Presence of LEPP in Ph and Pt on early contrast-enhanced computed tomography was independently associated with increased mortality in SAP. These patients require close observation to ensure timely and adequate intervention.